Tujuan Pendidikan Islam Perspektif Al-Quran Dan Hadis: Isu dan Strategi Pengembangan Pendidikan Islam - Tara Putri Mortalisa; Abdurrazzaq; Kristinaimron (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Given the importance of Islam in education, Islam has its own goals and reasons in dealing with the problem of terrorism. Therefore, this article will highlight the purpose of Islam, which is to encourage people to appreciate education. Where, instead of relying only on one book of tafsir, several books of tafsir are consulted. It also includes several hadiths related to the purpose of education, such as understanding the value of education in Islam. During the analysis, many characteristics of Muslim students were compared and the goals of Islamic education were emphasized. So, the various views of modern western education figures are a comparison in the study of educational objectives from the perspective of the Quran and Hadith.